Cu(II)-Catalysed Hydrocarboxylation of Imines Utilizing CO2 to Synthesize α-Unsaturated Aminocarboxylic Acids - Allen T. Gordon; Eric C. Hosten; Adeniyi S. Ogunlaja (MDPI AG, 2022)
Here, we report the Cu(II)-photocatalysed hydrocarboxylation of imines (C=N) from a series of synthesized Schiff Base derivatives, namely (E)-1-(4-((4-methylbenzylidene)amino)phenyl)ethanone, (E)-1-(3-((5-bromo-2-hydroxybenzylidene)amino)phenyl)ethanone, (E)-4-((5-bromo-2-hydroxybenzylidene)amino)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one, and (E)-1,5-dimethyl-4-((4-methylbenzylidene)amino)-2-phenyl-1H-pyrazol-3(2H)-one, with carbon dioxide (CO2) to generate disubstituted amino acids. Under mild conditions (atmospheric pressure of CO2, room temperature, and 30 W Blue LED light), good to excellent yields confirming the formation of substituted amino acid unsaturated acid derivatives were obtained. Single crystal X-ray diffraction (SC-XRD) and UV-Vis diffuse reflectance spectroscopy (UV-Vis-DRS) confirmed the square pyramidal geometry of the Cu(II) photocatalyst. Docking and DFT calculations of the substituted amino acid unsaturated acid derivatives showed their potential as antimicrobial molecules.